Unusual Extra-Axial and Extracranial Recurrence in an IDH Mutant Astrocytoma: A Case Report - Nair, Swetha M.; Sahu, Arpita; Prasad, Apurva; George, Asha Mary; Goel, Atul; Gupta, Tejpal (Indian Journal of Radiology and Imaging, 2023)
Isocitrate dehydrogenase mutant gliomas generally have a better prognosis than their wild-type counterpart. Recurrences are generally within the radiation field in the primary tumoral bed. Remote recurrence is uncommon and is usually intraparenchymal. Transformation to a higher grade has been observed with TP53 mutants. Presentation of glioma as an extra-axial lesion is extremely uncommon. No such cases of remote intracranial extra-axial recurrence have been reported in the literature. We describe the unique imaging findings in this case and attempt to formulate possible diagnoses. Intraoperative and pathological findings confirmed this unusual recurrence pattern.
Keywords: extra-axial; extracranial; recurrence; IDH mutant; glioma; metastases; astrocytoma